Occlusions in dendritic flow networks - Miguel (2019)
The shape and structure of flow networks is a topic of long-standing interest in natural and technological systems. Observations suggest that real-world flow networks may exhibit partial occlusions in paths (e.g., tubes, vessels). Here, dendritic patterns of fluid streams are viewed as a porous material, and the effect of obstructed paths in these networks designed for fluid flow under uniform and constant heat fluxes is investigated. Analytical approaches are presented that explicitly show the roles played by the network structure, the number of obstructed paths, and the geometrical place in which obstructions occur, on fluid flow properties. Structural features of bifurcating flow networks under laminar constant and pulsatile flows are analyzed. Our approaches provide several insights into the effect of paths structural parameters, and the effect of place where obstructions occur that can enlighten our understanding of network flow response.